Pelaksanaan Manajemen Dan Administrasi Kelas 7B Di SMP Negeri 6 Banjarmasin - Ridwan, Mohammad; Herdi, Herdi; Kia Rahman, Radit; Rahman, Anggia; Azhari, Muhammad; Suhaimi, Suhaimi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to provide an in-depth description of the implementation of classroom management and administration at SMP Negeri 6 Banjarmasin, particularly in Class VII B under the supervision of Mrs. Tri Widia Ningsih, S.Pd. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The study focused on three main aspects: the implementation of classroom management, the execution of classroom administration, and the teacher’s role as a learning manager. The findings reveal that the teacher successfully implemented effective classroom management strategies, which include the physical arrangement of the classroom, social interaction management, and the reinforcement of student discipline. A conducive and interactive learning environment was achieved through open two-way communication between teacher and students. In terms of administration, the teacher demonstrated good competence in managing both academic and non-academic records. The use of digital technology, such as Microsoft Excel and Google Drive, served as an important innovation that enhanced efficiency and accuracy in administrative documentation. Overall, the implementation of classroom management and administration at SMP Negeri 6 Banjarmasin was effective and professional. The teacher acted as a manager, administrator, motivator, and role model for students. This research highlights the importance of collaboration among teachers, students, and the school in fostering efficient, character-based, and sustainable learning.